OUTCOMES OF CVD PATIENTS WITH T2DM AND CKD IN THE ICU: A 3-MONTH RETROSPECTIVE COHORT STUDY - Harisa Mardiah; Tasya Epifania Sembiring; Rahayu Septiarini; Akhmad Hidayat; Rahmawati Rahmawati (Universitas Airlangga, 2026)
Introduction: Cardiovascular disease (CVD) is a leading global cause of death, often complicated by comorbid type 2 diabetes mellitus (T2DM) and chronic kidney disease (CKD), known collectively as Cardiovascular–Renal–Metabolic (CaReMe) conditions. These comorbidities significantly increase mortality and ICU burden, yet their combined impact on outcomes in intensive care remains underexplored. Despite their high prevalence, especially in critically ill patients, limited studies have focused on this triad in ICU settings. This study aims to address this gap by evaluating outcomes of ICU-admitted CVD patients with T2DM and CKD. Methods: A retrospective cohort study was conducted over three months in the ICU of Bidadari Batubara Hospital. Data from 86 CVD patients with T2DM and CKD were analyzed. Using purposive sampling, clinical data were retrieved from medical records. Statistical tests assessed associations between comorbidities and in-ICU mortality. Results: The study found high mortality rates in patients with CVD and comorbid T2DM and CKD. Patients with both conditions had a 64.9% mortality rate, a 2.07-fold increased risk of mortality compared to those with T2DM only (31.3%) (95% CI: 0.96-4.44), and a 1.53-fold increased risk compared to those with CKD only (42.4%) (95% CI: 0.96-2.43). A significant association was found between outcomes of CVD patients and comorbidities (p<0.001), with a positive correlation. Conclusions: Previous studies emphasize the impact of comorbidities on CVD outcomes; this study confirms that T2DM and CKD significantly increase ICU mortality, justifying targeted interventions to mitigate risk and improve outcomes in critically ill CVD patients.